PENGARUH JENIS KELAMIN DAN PENGETAHUAN TERHADAP PERILAKU JAJAN ANAK SEKOLAH DASAR - Pitriyanti, Luh; Septiati, Yosephina Ardiani; Putri, Annisa Pratiwi; Karmini, Mimin (Poltekkes Kemenkes Bandung, 2024)
Children tend to eat unhealthy foods or snacks in the school environment. This is caused by factors such as a lack of knowledge about healthy food and minimal access to healthy food choices in the school environment. This research aimed to analyze the influence of gender and knowledge on elementary school children's snacking behavior. This research was conducted in February-September 2023. This research is quantitative study with a cross-sectional design. The population is students in grades 4-6 in all state elementary schools in Bukit Bestari District, Tanjungpinang City. The sample was determined using simple random sampling by drawing lots from 10 schools and classes in all research locations. 30 students from grades 4-6 were selected from each school to obtain 300 students as samples. Analysis was carried out using the Chi-Square test with a confidence level of 95%. The results of this study show that there is no influence between gender and the snack food eating behavior of school children (p=0.284), and there is an influence between the level of knowledge and the snack food eating behavior of school children (p=0.002). This research concluded that there is no influence between gender and there is an influence between the level of knowledge and the behavior of eating snacks among school children. Students with less knowledge are at risk of having poor behavior in consuming PJAS 3,863 times. Increasing knowledge by providing counseling and practicing bringing snacks prepared from home needs to be done.